Harmonisasi Mahasiswa di tengah Adanya Heterogenitas Sosial di Jurusan PPKn FIS UNIMED - Apni Nurita Saragih; Fahreza Rizki Tabrani; Fadillah Melani Putri; Putri Yohan Damanik; Julia Ivanna (Universitas Muhammadiyah Enrekang, 2023)
Heterogeneous students from various backgrounds have their own challenges in creating harmony on campus. The purpose of this study was to analyze the factors that influence student harmonization in the midst of social heterogeneity in the Pancasila and Citizenship Education Department( PPKN), Faculty of Social Sciences( FIS) Muhammadiyah University( UNIMED). This study uses a qualitative approach by using observation and making a questionnaire in the form of a Google form link which will be filled out by students. The results showed that the factors that influence student harmonization in the midst of social heterogeneity in the PPKN FIS UNIMED Department are social interaction, fair rewards, understanding of culture, ethics, and norms, as well as the facilities available.